THE IMPACT OF ROAD GRADIENT AND TRUCK COMPOSITION ON THE TOLL ROAD TRAFFIC PERFORMANCE - Yusuf, Nahry; Sudrajat, Dwi Setiyadi (PLANNING MALAYSIA, 2018)
Jakarta Outer Ring Road (JORR) is a toll road system that circles the outskirts of Jakarta, where the purpose of this road is to reduce congestion on the streets in Jakarta city centre. However, the high composition of trucks in JORR resulted in congestion of the road, which is hypothesized as attributed by the gradient of this road. This study aims to evaluate the impact of road gradient on truck and the overall traffic performance. Using data obtained from 24-hour traffic recording on selected JORR section, a VISSIM model was constructed to simulate traffic performance on some combinations of traffic and gradient conditions. In terms of macroscopic view point of traffic stream, the simulations showed that road gradient alone insignificantly affected truck speed, as well as the overall traffic speed. Instead, truck composition had more effect on the traffic speed rather than the gradient. In a particular composition of trucks different gradients did not significantly affect traffic speed differently. This implies that any policy to restrict truck access to toll road should depend mainly on the composition of truck itself, not the gradient of the road.